Evaluating Satisfaction and Self-Confidence among Nursing Students in Clinical Simulation Learning - Sara Moreno-Cámara; Henrique da-; Laura Parra-Anguita; Belén Gutiérrez-Sánchez (MDPI AG, 2024)
Background: Clinical simulation is effective in nursing student education, fostering autonomous learning and critical skill development in safe environments. This method is adaptable to dynamic educational approaches and integrates technology. Satisfaction and self-confidence are key elements in its evaluation. The general objective of this research was to describe the levels of satisfaction and self-confidence among undergraduate nursing students regarding the use of clinical simulation in the field of family and community nursing. Methods: A cross-sectional descriptive study was conducted at the University of Jaén, Spain, during the 2023/2024 academic year. Data on sociodemographic aspects, satisfaction, and self-confidence were collected using a validated instrument. The statistical analysis included central measures, dispersion, and frequencies, with confidence intervals. Results: The study involved 96 students in scenario 1 (family assessment) and 97 in scenario 2 (family intervention), with the majority being women. In scenario 1, the mean satisfaction score was 4.38 out of 5, and self-confidence was scored 4.44 out of 5. Prior preparation time correlated significantly with higher levels of satisfaction and self-confidence. In scenario 2, the mean scores were slightly higher but not statistically significant. Conclusions: Our study demonstrated high levels of satisfaction and self-confidence among nursing students following clinical simulations. Prior preparation was associated with better outcomes, and the quality of the simulation positively impacted the results.